PENDIDIKAN BAGI ANAK PMI DI SANGGAR BELAJAR NEGERI SEMBILAN MALAYSIA DALAM MENGEJAR KETERTINGGALAN PELAJARAN - Zaitun Khairani; Daniati Putri; Syahrizal; Nila Sari Siagian; Surono ZR; Andri Nurwandi (Cattleya Darmaya Fortuna, 2026)
The implementation of the International Community Service Program (KKNI) at the learning center aims to improve academic quality while fostering students’ character, nationalism, environmental awareness, and cultural identity. This study employed a par- ticipatory-collaborative method involving students, teachers, learners, and parents in de- signing and carrying out the activities. The results show improvements in literacy and nu- meracy skills at the lower grades, mastery of mathematics and natural sciences at the upper grades, as well as a deeper understanding of tajwid through tahsin Al-Qur’an. Nationalism and physical fitness were strengthened through routine activities, while environmental and cultural awareness developed through greening programs, fieldwork, and collective dodol making. Thus, KKNI has proven to make a holistic contribution to academic enhancement, character building, and the strengthening of students’ cultural identity.